2017
DOI: 10.17576/3l-2017-2303-01
|View full text |Cite
|
Sign up to set email alerts
|

Using the Flipped Model to Foster Thai Learners’ Second Language Collocation Knowledge

Abstract: In recent years, interest in flipped classrooms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…Possible answers might be that the errors occurred because the students were unaware of contexts when selecting the appropriate prepositions or they might have lacked the knowledge about some aspects of collocations, i.e., "adjective + preposition" or "verb + preposition." Another possible cause could be in accordance with the study of Suranakkharin (2017). He found that collocation competence was one of the problematic learning areas of Thai university students.…”
Section: Translation Error Analysissupporting
confidence: 59%
“…Possible answers might be that the errors occurred because the students were unaware of contexts when selecting the appropriate prepositions or they might have lacked the knowledge about some aspects of collocations, i.e., "adjective + preposition" or "verb + preposition." Another possible cause could be in accordance with the study of Suranakkharin (2017). He found that collocation competence was one of the problematic learning areas of Thai university students.…”
Section: Translation Error Analysissupporting
confidence: 59%
“…Although assignment instructions were made available in what were deemed highly visible parts of the interface, some students may have required additional guidance in navigating it. Additional guidance may have also been necessary because it has been noted Thai students may not be used to operating on their own in an active learning context, such as one created by using a flipped classroom approach (Suranakkharin, 2017;Thaichay & Sitthitikul, 2016). Suranakkharin (2017), in a study of using the flipped classroom approach to help Thai EFL learners master English collocations, discussed the importance of having a facilitator in the success of flipped classroom instruction and subsequent student perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…One of these approaches include the use of flipped teaching, where the learning materials are delivered outside class time through interactive means, and class times are solely used for practice. Suranakkharin (2017) revealed that students who attended flipped classes have higher English collocations in the post-tests than in the pre-tests. However, results of the post-tests reveal that the outcomes of flipped and conventional classrooms do not substantially differ.…”
Section: Other Strategies Used To Address Collocational Competencementioning
confidence: 97%
“…Besides the corpus-based and traditional methods used to address collocational competence, some researchers (Suranakkharin, 2017;Nagy, 2020;Özcan & Kert, 2020;Ginanti, 2020) proposed other methodologies that can help counter the lack of collocational competence amongst English language learners.…”
Section: Other Strategies Used To Address Collocational Competencementioning
confidence: 99%